Conceptual understanding and misconceptions of the human digestive system in elementary school: insights from a four-tier diagnostic test - Navalia Dewi Ernamasari (Nashir Al-Kutub Indonesia, 2025)
The purpose of this study was to analyze the form and level of misconceptions of fifth grade elementary school students on the material of the human digestive system with the Four-Tier Diagnostic Test instrument. A descriptive quantitative method was used and with a quantitative approach. The Four-Tier Diagnostic Test was used to identify misconceptions in more depth by analyzing students’ answers, reasons, and level of confidence in the answers given. This study involved 27 students of class V A of Djama’atul Ichwan Elementary School in Surakarta, Central Java, Indonesia who were purposely selected. The results of the analysis show that the overall misconceptions of students are at a level of 18% which means that the level of misconception is low, but still in each specific sub-concept there are misconceptions, the highest misconceptions are found in several items on the sub-material of digestive organs and their functions with a percentage of item misconceptions of 37%. This research suggests that conceptual diagnosis-based learning methodologies and contextual learning media, like augmented reality media and practical kits, are necessary to reduce misconceptions. This research also confirms that the Four-Tier Diagnostic Test is an effective diagnostic tool for detecting science misconceptions at the primary school level.